2007
DOI: 10.1051/0004-6361:20066820
|View full text |Cite
|
Sign up to set email alerts
|

A computer program for fast non-LTE analysis of interstellar line spectra

Abstract: Aims. The large quantity and high quality of modern radio and infrared line observations require efficient modeling techniques to infer physical and chemical parameters such as temperature, density, and molecular abundances. Methods. We present a computer program to calculate the intensities of atomic and molecular lines produced in a uniform medium, based on statistical equilibrium calculations involving collisional and radiative processes and including radiation from background sources. Optical depth effects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
841
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,417 publications
(874 citation statements)
references
References 57 publications
32
841
1
Order By: Relevance
“…Simulations with the line escape probability program RADEX (van der Tak et al 2007), indicate that these observed CO(2-1)/CO(1-0) line ratios of order unity can be obtained for gas kinetic temperatures ranging from 20 to 500 K, for H 2 gas densities >10 2.5−3 cm −3 and N CO /ΔV > 10 15 cm −2 km s −1 (right panel of Fig. 2).…”
Section: Line Ratiosmentioning
confidence: 90%
“…Simulations with the line escape probability program RADEX (van der Tak et al 2007), indicate that these observed CO(2-1)/CO(1-0) line ratios of order unity can be obtained for gas kinetic temperatures ranging from 20 to 500 K, for H 2 gas densities >10 2.5−3 cm −3 and N CO /ΔV > 10 15 cm −2 km s −1 (right panel of Fig. 2).…”
Section: Line Ratiosmentioning
confidence: 90%
“…The escape probability formalism used to treat this optically thick situation was first applied to molecular clouds by Scoville & Solomon (1974) and Goldreich & Kwan (1974) and is now routinely used to analyse interstellar molecule excitation (often called large velocity gradient [LVG], non-thermal equilibrium [non-LTE] analysis; see, e.g., van der Tak et al (2007) and their publicly available RADEX code) † . One of the biggest advantages of the LVG formalism is that it permits treatment of the coupled radiative transfer and molecular excitation as a local problem -a fact probably not fully appreciated by current routine users of these codes.…”
Section: Molecular Excitationmentioning
confidence: 99%
“…To this end, we used the non-LTE excitation code RADEX with an escape probability formalism for the radiative transfer ( Van der Tak et al 2007) coupled with the LAMDA database . Methanol is the species detected in the largest number of lines.…”
Section: Physical Properties Along the B1 Bow Shockmentioning
confidence: 99%